PRINSIP HUKUM YANG BERKEADILAN EKONOMI SOSIAL DAN BUDAYA DALAM MASYARAKAT UMUM DI KABUPATEN MERAUKE - Ruloff Fabian Yohanis Waas (Universitas Musamus, Merauke, Papua, 2014)
Concept social justice expand along with growth of human being human right where in is in perpective of HAM, human being realize that insufficient only requiring freedom, however also have to make balance to with prosperity especially pasca formulation of international kovenan of economic rights, culture and social.This research aim to to know how far execution in ekosob with social justice principle in common society in Sub-province of Merauke. Research method the used is research method qualitative by using approach in the form of obtained data directly from population and sampel through interview, exhaustively. Technique analyse data the used is analytical descriptive, this meant to obtain;get good picture, clear and can give data of sedetail possible about accurate object.Result of this research indicate that ekosob with social justice principle in common society in Sub-province of Merauke not yet been executed better according to trust of UU No.14 year 1970 About Fundamental of judgement, The mentioned happened because caused many matter one of them because laymen still society to way of the solving of the problem of society and law not yet understood how mechanism of is way of denunciating in law dispute.